2018
DOI: 10.1093/jme/tjx254
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Species (Diptera: Culicidae) Diversity from Ovitraps in a Mesoamerican Tropical Rainforest

Abstract: Mosquito sampling using efficient traps that can assess species diversity and/or presence of dominant vectors is important for understanding the entomological risk of mosquito-borne disease transmission. Here, we present results from a survey of mosquito species sampled with ovitraps in a neotropical rainforest of Costa Rica. We found the method to be an efficient sampling tool. With a total sampling effort of 29 traps, we collected 157 fourth-instar larvae and three pupae belonging to eight mosquito taxonomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
2
19
0
2
Order By: Relevance
“…The greatest diversity of immature mosquitoes species found at the edge of the forest suggested a change in the habitat of these populations, and similar results were reported in the studies of Steiger et al [55]. Chaverri et al [49], in their study of immature mosquito fauna in different environments, observed no difference in mosquito populations between the primary and secondary forest environment. Ribeiro et al [51] suggested that environmental stresses increase the number of niches favorable to mosquitoes and, thus, promote the greater diversity of mosquitoes in anthropogenic environments.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The greatest diversity of immature mosquitoes species found at the edge of the forest suggested a change in the habitat of these populations, and similar results were reported in the studies of Steiger et al [55]. Chaverri et al [49], in their study of immature mosquito fauna in different environments, observed no difference in mosquito populations between the primary and secondary forest environment. Ribeiro et al [51] suggested that environmental stresses increase the number of niches favorable to mosquitoes and, thus, promote the greater diversity of mosquitoes in anthropogenic environments.…”
Section: Discussionsupporting
confidence: 80%
“…(Melanoconion) spp., were the second and third species with largest number of specimens. Chaverri et al [49] also reported the dominance of Tr. digitatum , collected in ovitraps in a forest region in Costa Rica.…”
Section: Discussionmentioning
confidence: 96%
“…Also, studies tend to concentrate in mosquito species of direct interest to humans (mainly as vectors of diseases) and therefore often fail to sample a large variety of habitat types. This is likely to constitute a major problem since many mosquito species are specifically associated with certain plants (Hoshi et al ., ; Cardoso et al ., ) or vegetation height (Julião et al ., ; Chaverri et al ., ). In fact, most mosquito species show strict ecological requirements (Golding et al ., ; Sallam et al ., ) related to their larval habitat (Blaustein & Chase, ; Juliano, ), resting and host blood feeding behaviour (Chaves et al ., ; Takken & Verhulst, ) that may predispose them to go extinct when introduced onto novel environments where those requirements are not present.…”
Section: Discussionmentioning
confidence: 97%
“…For both vectors, timely surveillance and control measures in endemic or high-risk locations for disease transmission requires sensitive methods to quickly detect changes in mosquito abundance. Surveillance is important also to detect the establishment of uncommon or invasive species in regions where they have not been reported (Hernandez-Avila et al 2013;Chaverri et al 2018). Urban and semi-urban larval habitats of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…These traps are safe, reusable, and inex-pensive (CDC 2017). For these reasons, ovitraps are one of the most practical tools for surveillance of container-inhabiting Aedes (Wu et al 2013;Codeço et al 2015;Chaverri et al 2018).…”
Section: Introductionmentioning
confidence: 99%